Analisis Willingness To Pay (WTP) Retribusi Sampah Rumah Tangga di Kabupaten Aceh Barat - Serly Riski Amanda; Fahmi Ichwansyah; Irwan Saputra (Jurnal Kesehatan Komunitas, 2023)
Willingness To Pay (WTP) can be interpreted as how much people are willing to pay.  However, there are several problems, namely until now the Willingness To Pay (WTP) waste retribution has not been maximized and this can be seen in the achievement of   Regional Original  Income  (PAD) for waste retribution.  Thus, the problem raised in this study is that the willingness to pay of the community to pay waste fees in West  Aceh Regency is still low. The purpose of this study is to determine the amount of Willingness to Pay (WTP) of waste retribution paid by households and the factors that affect the WTP of household waste in West  Aceh Regency.  This research is a type of quantitative research with a cross-sectional study approach. The samples in this study were 378 heads of families, namely  261 people in the  Johan Pahlawan sub-district and 117 people in the Meureubo sub-district. The sampling technique was carried out using  Krejcie and Morgan Table. Data was collected using a questionnaire, while the statistical test used was logistic regression using stata. The results showed that the Willingness to Pay (WTP) waste retribution paid by households in West  Aceh Regency was  Rp. 14,542 and the factors related to the  WTP of household waste in West   Aceh Regency partially  (partially) namely income  (p-value = 0.001) and public perception in waste management  (p-value  = 0.031) and the relationship between income and community perception in waste management simultaneously with  WTP for household waste retribution  (p-value below  0.05).